Explanation for the Increase in High‐Altitude Water on Mars Observed by NOMAD During the 2018 Global Dust Storm. Issue 7 (25th March 2020) - Neary, L.; Daerden, F.; Aoki, S.; Whiteway, J.; Clancy, R. T.; Smith, M.; Viscardy, S.; Erwin, J.T.; Thomas, I. R.; Villanueva, G.; Liuzzi, G.; Crismani, M.; et al.
Abstract: The Nadir and Occultation for MArs Discovery (NOMAD) instrument on board ExoMars Trace Gas Orbiter measured a large increase in water vapor at altitudes in the range of 40–100 km during the 2018 global dust storm on Mars. Using a three‐dimensional general circulation model, we examine the mechanism responsible for the enhancement of water vapor in the upper atmosphere. Experiments with different prescribed vertical profiles of dust show that when more dust is present higher in the atmosphere, the temperature increases, and the amount of water ascending over the tropics is not limited by saturation until reaching heights of 70–100 km. The warmer temperatures allow more water to ascend to the mesosphere. Photochemical simulations show a strong increase in high‐altitude atomic hydrogen following the high‐altitude water vapor increase by a few days. Plain Language Summary: The ExoMars Trace Gas Orbiter (TGO) is currently in orbit around Mars measuring the composition of the atmosphere. TGO was able to make observations before, during, and after a large planet‐encircling dust storm that occurred from June to August 2018. The TGO measurements provide the first opportunity to observe how water vapor is distributed with height in the atmosphere during a global‐scale dust event. It was found that there was a large increase in water vapor very high (40–100 km) in the atmosphere during the dust storm. Using a three‐dimensional numerical model of the Mars atmosphere, we found that when dust from the storm is transported up to levels above 40 km, it warms the atmosphere due to solar absorption, and this in turn prevents ice clouds from forming at heights of 40–60 km and allows more water vapor to ascend to greater heights in the atmosphere. This is of interest in terms of the planetary evolution, as water molecules at greater heights are more readily dissociated by sunlight and lost from the atmosphere. This is an important factor for understanding the changes that have occurred since the period when surface features on Mars indicate that liquid water was present. Key Points: Transport of water vapor is simulated during the 2018 global dust storm on Mars in the GEM‐Mars General Circulation Model The simulation explains NOMAD observations of enhanced high‐altitude water abundances during the global dust storm The vertical distribution of dust is a key factor for the transport of water vapor through the equatorial hygropause